Zinc-protoporphyrin content in commercial Parma hams is affected by proteolysis index and marbling. (May 2018) - Bou, Ricard; Llauger, Mar; Arnau, Jacint; Fulladosa, Elena
Abstract: The contents of zinc-protoporphyrin (ZnPP) and heme in twenty-four sliced Parma hams made without the addition of curing agents were determined. Expressed on a dry weight basis, ZnPP averaged 45 mg/kg and ranged from 23 to 85 mg/kg. The heme content averaged 37 mg/kg on a dry matter basis and ranged from 17 to 73 mg/kg. A Principal Component Analysis (PCA) and Partial Least Squares (PLS) regression analyses were carried out to examine the existing correlations between these pigments and various physicochemical parameters in the final product. PCA showed the existence of associations between ZnPP, sensory redness and salt content. PLS suggests that the conversion of ZnPP from heme is facilitated in those hams with a higher proteolysis index and higher marbling. Highlights: Typical contents of zinc-protoporphyrin (ZnPP) in commercial Parma ham were reported. ZnPP content was positively correlated with redness and salt content. Proteolysis and marbling were related with higher conversions of heme into ZnPP.